Runoff Potential of Nadis in Different Landforms in the Guhiya Catchment, Western Rajasthan - Vangani, N S (Annals of Arid Zone, 2016)
Small earthen embankment/dug out ponds called nadis are the principal drinking water sources in the Indian desert. The structure and functioning of this ancient practice is studied in relation with geomorphic units to design for greater storage and better utilization of runoff water. The interrelationship between runoff volume and catchment area in different landforms have been explained by regression equations. It is revealed, that in buried pediments, the nadis should be constructed under catchment slopes of less than 1%.